2021
DOI: 10.1111/ped.14635
|View full text |Cite
|
Sign up to set email alerts
|

Association between preterm birth and maternal allergy considering IgE level

Abstract: Background The aim of this study was to explore the association between maternal allergies and preterm birth by different total immunoglobulin E (IgE) levels. Methods Data of 81 791 pregnant women from the Japan Environment and Children’s Study, a prospective birth cohort, were used. Maternal allergic diseases, including a history of bronchial asthma (BA), atopic dermatitis (AD), and allergic rhinitis (AR), were obtained by self‐administered questionnaires. Total serum IgE levels were measured at the first tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…7 Low humidity may be related to a high incidence of AD. 8 Relating birth cohort data [9][10][11][12] and metrological data 13 may help answer the question of how birth month is associated with the incidence of AD. Therefore, this study aimed to investigate how birth month is associated with the incidence of AD.…”
Section: Introductionmentioning
confidence: 99%
“…7 Low humidity may be related to a high incidence of AD. 8 Relating birth cohort data [9][10][11][12] and metrological data 13 may help answer the question of how birth month is associated with the incidence of AD. Therefore, this study aimed to investigate how birth month is associated with the incidence of AD.…”
Section: Introductionmentioning
confidence: 99%
“… Previous studies showed that guinea pigs that were sensitized with chicken egg ovalbumin were at greater risk to deliver a preterm pup than those challenged with normal saline [ 18 , 61 ]. Prior studies have suggested an association between patients with an allergic disease, such as asthma or allergic rhinitis, and increased preterm delivery [ 69 71 ]. Several case reports have shown that exposure to an allergen can induce uterine contractions and that these contractions are ameliorated after the treatment of anaphylaxis together with the standard treatment of preterm labor pain [ 22 , 72 74 ].…”
Section: Allergy As a Mechanism Of Disease Of Preterm Labormentioning
confidence: 99%
“…Prior studies have suggested an association between patients with an allergic disease, such as asthma or allergic rhinitis, and increased preterm delivery [ 69 71 ].…”
Section: Allergy As a Mechanism Of Disease Of Preterm Labormentioning
confidence: 99%
“…In this issue of the journal, Kojima et al 4 reported the association between preterm birth and maternal allergy using JECS data and found that maternal BA and AR were associated with an increased risk of threatened abortion and preterm labor (PTL). In contrast, high total IgE levels were associated with a decreased risk of PTL.…”
mentioning
confidence: 99%